1981
DOI: 10.1099/0022-1317-55-2-305
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Herpetic Lesions to Malignancy by Ultraviolet Exposure and Promoter Application

Abstract: SUMMARYMany lines of evidence exist associating herpes simplex virus (HSV) with the development of carcinoma, but much of this evidence is anecdotal or associative in nature and does not prove a cause and effect. The purpose of this research was to investigate the oncogenic potential of HSV type 2 (HSV-2) in vivo. A mouse model for lip carcinogenesis was designed to combine HSV-2 infection, u.v. exposure and tetradecanoyl-phorbol-acetate (TPA) application. HSV-2 inoculation on to abraded mouse lips was capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1984
1984
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…On the other hand, with increased time of latency, irreversible and malignant lesions would have had a better chance to develop. The difference in tumour incidence between this study and the one by Burns & Murray (1981) might indicate that HSV-2 has a more potent initiating capacity than HSV-1. However, the different methods of inactivation of HSV after infection might well have been an important factor.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…On the other hand, with increased time of latency, irreversible and malignant lesions would have had a better chance to develop. The difference in tumour incidence between this study and the one by Burns & Murray (1981) might indicate that HSV-2 has a more potent initiating capacity than HSV-1. However, the different methods of inactivation of HSV after infection might well have been an important factor.…”
Section: Discussioncontrasting
confidence: 58%
“…However, if the results for the animals that received HSV inocula and TPA, with or without acyclovir (groups I and II), are added together, the differences in incidence of lip tumours as well as of all tumours are statistically significant (P ~< 0-05) when compared with animals not receiving this combined treatment (groups III, IV and V). Burns & Murray (1981) used a classical model of initiator, cofactor and promoter to study the incidence of tumours in the treated area, i.e. the mouse lip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that treatment of recipient cells with chemical carcinogens or UV irradiation of in vivo infected areas signi ficantly enhances the transforming or onco genic potential of HSV [22,23]. This may indicate that HSV acts as a cofactor in the transformation process and does not need to be continuously present or expressed.…”
Section: Discussionmentioning
confidence: 96%
“…The enhancing effects of chemical and physical carcinogens on animal cell transformation by oncogenic viruses have been well documented in adenovirus type 12, SV (simian virus) 40, polyoma and retrovirus systems. It has also been possible to demonstrate synergism between herpes simplex virus type 2 (HSV-2), UV irradiation, and tumor promotion in the development of malignancy (Burns and Murray, 1981). These results may well have been inferred from the in vitro experiments of Johnson (1982), demonstrating the ability of chemical carcinogens to enhance HSV-2induced 3T3 mouse cell transformation.…”
mentioning
confidence: 97%